PEMBERDAYAAN PETANI PADI DALAM PEMASARAN BERAS KEMAS DI DESA KADUGENEP KECAMATAN PETIR KABUPATEN SERANG - Rizqi Maulana Syifa; Wasrob Nasruddin; Achdiyat Achdiyat (Jurnal Inovasi Penelitian, 2020)
Rice commodity is one of the main commodities being cultivated by farmers in Kadugenep Village. .various kinds of agricultural activities carried out by rice farmers in Kadugenep Village, in carrying out agricultural activities not only on production activities or cultivation of plants, but how to market agricultural productsin order to generate profits that can prosper farmers in terms of the economy.the assessment activities have been carried out from March 1 to June 30, 2020, with a total sample of 32 people. Data mining is done by interviews, questionnaires that have been tested for validity and reliability, as well as direct observation. .farmer empowerment levels were analyzed descriptively, factors related to empowerment were analyzed using the Spearmean Rank Correlation, and counseling strategies were analyzed using Kendal's Wbased on the results obtained from interviews and questionnaires given to respondents, showed that 5 people (15.6%) of respondents stated helpless, while 27 people (84.4%) respondents stated helpless. factors related to the role of the government (X2.1) of 0,000 and the role of advisors (X2.2) of 0.001 have a significant relationship to the empowerment of rice farmers in marketing rice packaging. strategies that can be done in increasing the empowerment of rice farmers in marketing rice from the results of the Kendall W analysis, namely by providing counseling about the function of cooperatives as a place for marketing products and functionspackaging with lecture, discussion and demonstration methods as well as extension media used, namely the provision of videos and folders.